Improving the water quality of iron‐containing ponds using fermented kitchen wastes. Issue 1 (17th November 2021) - Yong, Ee Ling; Halim, Khairunnisa Abdul; Liong, Vivien Yu Fen; Tee, Michelle Lee Kiau; Yong, Zhi Yuan; See, Hong Heng; Syafiuddin, Achmad
Abstract: To elucidate the efficacy of eco‐enzyme in mediating contaminated waters, an onsite investigation was conducted spanning over a 5‐month duration on three ponds receiving iron‐containing groundwater continuously. Eco‐enzyme was applied at designated dosages and time. Water samples were collected fortnightly for in situ monitoring of water quality. Parameters determined included total suspended solids (TSS), pH, alkalinity, chemical oxygen demand (COD), biochemical oxygen demand (BOD5 ), ammoniacal‐nitrogen (NH3 ), and dissolved oxygen. During the investigation, eco‐enzyme application was halted for nearly a month owing to the enforcement of Movement Control Order to curb the rising Covid‐19 cases. The results revealed that the application of eco‐enzyme has improved the overall water quality of the three ponds. A 99.9% of TSS removal was achieved. For the other parameters measured, the concentration fluctuated over time and the water quality status of the pond interchanged between slightly polluted and clean. The elevation of the water quality was largely dependent on the frequency of the eco‐enzyme application. This study, therefore, concludes that eco‐enzyme possessed the capability to enhance the quality of contaminated water.